Implementasi Perlindungan Hukum Terhadap Anak Korban Kekerasan Seksual Berdasarkan Hukum Positif Dan Perspektif Maqashid Syariah - Dipayanti, Ashylla Zabrina; Iksan, Muchamad (RIO LAW JURNAL, 2024)
Children as members of the younger generation are a substitute for the country's independence aspirations and the potential for human resources for the founding of the country. Recently, sexual crimes have not only happened to adults but also to children. Legal protection is the most important element in a legal state, because legal protection is the right of every citizen and the obligation of the state as the organizer of protection. This article aims to describe legal protection for child victims of sexual violence from the perspective of State regulations and Maqashid Syariah. The research method used in this article is normative juridical, a way of analyzing library materials, namely primary and secondary legal materials. The results of the analysis show that the concept of child protection which is accommodated by the State is manifested in various regulations governing the provision of severe sanctions against perpetrators of abuse of minors as stated in Articles 59 and 81-82 of Law no. 35 of 2014 concerning Amendments to Law no. 23 of 2002 concerning Child Protection, Articles 289-296 of the Criminal Code. Legal protection for child victims of sexual violence viewed from the Maqashid Syariah perspective is in a very urgent position, namely at the dharuriyyah (primary) level. The benefit of the world and the hereafter is oriented towards upholding the maintenance of primary legal objectives, namely: hifdz al-din, hifdz an-nafs, hifdz al-aql, hifdz an-nasl and hifdz al-mal. Its existence is absolute in humans so its perfection must be guarded and maintained.